High-thermal-stability Al-Mn-Cu alloy, preparation method and application thereof

CN122979709APending Publication Date: 2026-10-27QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES) +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611157554.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-31
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

为了进一步提高耐热Al-Zr导电合金的综合性能,可以使用Sc、Er、Yb等元素对其进行微合金化处理,微合金化后,虽然合金强度提高,但其耐热性并没有显著改善,因此,如何进一步提高耐热性成为耐热导线发展的瓶颈

Benefits of technology

本发明通过调控Al-Mn-Cu合金中的元素配比、冷轧变形结合后续时效处理,使固溶于铝基体的Mn、Cu元素充分脱溶析出;该工艺可在铝基体内析出大量细小弥散的T相(Al20Cu2Mn3)强化颗粒,T相能够在高温下有效钉扎晶界、阻碍位错滑移,从而制备具有优异耐热性能的Al-Mn-Cu合金。实验结果表明,本发明提供的Al-Mn-Cu合金的耐热温度达到550℃以上,同时具有较高的强度和导电率。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122979709A_ABST
    Figure CN122979709A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of aluminum alloy, in particular to a high-thermal-stability Al-Mn-Cu alloy and a preparation method and application thereof. By regulating the element ratio in the Al-Mn-Cu alloy, cold rolling deformation and subsequent aging treatment, the Mn and Cu elements dissolved in the aluminum matrix are fully precipitated; the process can precipitate a large number of fine and dispersed T phase (Al 20 Cu2Mn3) strengthening particles in the aluminum matrix, and the T phase can effectively pin the grain boundary and hinder dislocation slip at high temperature, thereby preparing an Al-Mn-Cu alloy with excellent heat resistance. Experimental results show that the heat resistance temperature of the Al-Mn-Cu alloy provided by the present application reaches 550 DEG C or above, and the alloy also has high strength and conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of aluminum alloy technology, specifically to a high thermal stability Al-Mn-Cu alloy, its preparation method, and its application. Background Technology

[0002] Aluminum alloys are widely used in overhead power lines due to their low density, high specific strength, and good machinability. However, increasing power transmission demands lead to higher conductor operating temperatures, which in turn degrade the mechanical properties of aluminum conductors and reduce the reliability of power lines. Therefore, the development of high-strength, high-conductivity, heat-resistant aluminum alloy conductor materials is imperative.

[0003] Currently, commonly used heat-resistant aluminum alloy conductors are Al-Zr alloys. The addition of Zr forms dispersed, fine L12 metastable nano-Al3Zr particles in the aluminum matrix, which hinders grain boundary movement, thereby increasing the recrystallization temperature of the aluminum alloy to 350~400℃, thus improving its heat resistance. To further improve the overall performance of heat-resistant Al-Zr conductive alloys, microalloying treatment can be performed using elements such as Sc, Er, and Yb. Although microalloying increases the alloy strength, its heat resistance is not significantly improved. Therefore, how to further improve heat resistance has become a bottleneck in the development of heat-resistant conductors. Summary of the Invention

[0004] To overcome the above problems, this invention provides a high thermal stability Al-Mn-Cu alloy, its preparation method, and its application.

[0005] To achieve the above technical objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a high thermal stability Al-Mn-Cu alloy, wherein the high thermal stability Al-Mn-Cu alloy comprises, by mass percentage, Mn 0.3 wt%~1.2 wt%, Cu 0.2 wt%~3 wt%, w(Cu) / w(Mn)≥0.77, Fe ≤0.2 wt%, Si ≤0.2 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al; The preparation method includes the following steps: Pure Al, pure Cu, and Al-10Mn were weighed according to their mass percentages, and alloyed to obtain a melt. The melt was then cast to obtain an as-cast Al-Mn-Cu alloy. The as-cast Al-Mn-Cu alloy was cold-rolled to deform it by 85-90%, and then aged to obtain a high thermal stability Al-Mn-Cu alloy.

[0006] In one or more embodiments, the temperature during alloy melting is 720~760°C.

[0007] Preferably, the alloy smelting method includes: Heat pure Al to 720~760℃, then add pure Cu and Al-10Mn, let stand and keep warm for 20~40 minutes to completely melt all the raw materials, stir evenly, and it is ready.

[0008] In one or more embodiments, a double-roll cold rolling mill is used for cold rolling deformation, with each pass having a deformation amount of 2% to 4%, and the final deformation amount of 85% to 90% is achieved through multiple passes of deformation.

[0009] In one or more embodiments, the aging treatment temperature is 300~450℃, and the aging treatment time is 75~100 h.

[0010] In one or more embodiments, the high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 0.7 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0011] In one or more embodiments, the high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 1.2 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0012] In one or more embodiments, the high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 1.6 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0013] In one or more embodiments, the high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 2.0 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0014] In a second aspect, the present invention provides a high thermal stability Al-Mn-Cu alloy, which is prepared by the preparation method described in the first aspect.

[0015] A third aspect of the present invention provides the application of the high thermal stability Al-Mn-Cu alloy described in the second aspect as an aluminum alloy conductor.

[0016] The beneficial effects of this invention are as follows: This invention achieves complete desolvation and precipitation of Mn and Cu elements dissolved in the aluminum matrix by controlling the element ratio in the Al-Mn-Cu alloy, combining cold rolling deformation with subsequent aging treatment; this process can precipitate a large number of fine and dispersed T phases (Al2O3- ... 20 Cu2Mn3) reinforced particles and the T phase can effectively pin grain boundaries and hinder dislocation slip at high temperatures, thereby preparing an Al-Mn-Cu alloy with excellent heat resistance. Experimental results show that the Al-Mn-Cu alloy provided by this invention has a heat resistance temperature of over 550℃, while also exhibiting high strength and electrical conductivity. Attached Figure Description

[0017] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.

[0018] Figure 1 The conductivity of different Al-Mn-Cu alloys in Examples 1 to 8 and the same Al-Mn-Cu alloy under different aging treatment times; Figure 2 The microhardness of different Al-Mn-Cu alloys in Examples 1 to 8 and the same Al-Mn-Cu alloy under different aging treatment times; Figure 3 The hardness residual rate of the samples prepared in Examples 1, 3, 5 and 7 at different heat exposure temperatures; Figure 4 The strength residual rate of the samples prepared in Examples 1, 3, 5 and 7 at different heat exposure temperatures; Figure 5 TEM microstructure of Al-0.8Mn-0.7Cu alloy aged at 400℃ for 100 h; Figure 6 TEM microstructure of Al-0.8Mn-2Cu alloy aged at 400℃ for 100 h. Detailed Implementation

[0019] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0020] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.

[0021] Aluminum alloys are widely used in overhead power lines due to their low density, high specific strength, and good machinability. However, increasing power transmission demands lead to higher conductor operating temperatures, which in turn degrade the mechanical properties of aluminum conductors and reduce the reliability of power lines. Therefore, the development of high-strength, high-conductivity, heat-resistant aluminum alloy conductor materials is imperative.

[0022] T phase (Al) 20 Cu2Mn3 is a heat-resistant phase with a complex orthorhombic crystal structure. This invention utilizes controlled elemental ratios in the Al-Mn-Cu alloy, combined with cold rolling deformation and subsequent aging treatment, to fully precipitate Mn and Cu elements dissolved in the aluminum matrix. This process can precipitate a large amount of fine, dispersed T-phase (Al2Mn3) within the aluminum matrix. 20 Cu2Mn3) reinforced particles and the T phase can effectively pin grain boundaries and hinder dislocation slip at high temperatures, thereby preparing an Al-Mn-Cu alloy with excellent heat resistance. Experimental results show that the Al-Mn-Cu alloy provided by this invention has a heat resistance temperature of over 550℃, while also exhibiting high strength and electrical conductivity.

[0023] To enable those skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below with reference to specific embodiments.

[0024] Example 1 High thermal stability Al-0.8Mn-0.7Cu alloy: The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 0.7 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0025] (1) Weigh out pure Al, pure Cu and Al-10Mn according to the mass percentage of the Al-0.8Mn-0.7Cu composition of the target alloy; Pure Al was heated to its melting temperature of 750°C, then pure Cu and Al-10Mn were added. The mixture was kept at this temperature for 30 minutes to allow all the raw materials to melt completely. The surface slag was removed and the mixture was stirred thoroughly. The melt was then poured into a steel mold and cast to obtain a cast Al-Mn-Cu alloy.

[0026] (2) The as-cast Al-Mn-Cu alloy was cold-rolled and deformed by 90%, and then aged to obtain a high thermal stability Al-Mn-Cu alloy.

[0027] The aging treatment temperature was 400℃, and the treatment time was 100 h.

[0028] Example 2 Compared with Example 1, the aging treatment temperature was 400°C, and the treatment time was 0 h, 5 h, 15 h, 35 h, 55 h, 75 h and 100 h.

[0029] Example 3 High thermal stability Al-0.8Mn-1.2Cu alloy: The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 1.2 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0030] (1) Weigh out pure Al, pure Cu and Al-10Mn according to the mass percentage of the Al-0.8Mn-1.2Cu component of the target alloy; Pure Al was heated to its melting temperature of 750°C, then pure Cu and Al-10Mn were added. The mixture was kept at this temperature for 30 minutes to allow all the raw materials to melt completely. The surface slag was removed and the mixture was stirred thoroughly. The melt was then poured into a steel mold and cast to obtain a cast Al-Mn-Cu alloy.

[0031] (2) The as-cast Al-Mn-Cu alloy was cold-rolled and deformed by 90%, and then aged to obtain a high thermal stability Al-Mn-Cu alloy.

[0032] The aging treatment temperature was 400℃, and the treatment time was 100 h.

[0033] Example 4 Compared with Example 3, the aging treatment temperature was 400℃, and the treatment time was 0 h, 5 h, 15 h, 35 h, 55 h, 75 h and 100 h.

[0034] Example 5 High thermal stability Al-0.8Mn-1.6Cu alloy: The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 1.6 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0035] (1) Weigh out pure Al, pure Cu and Al-10Mn according to the mass percentage of the Al-0.8Mn-1.6Cu component of the target alloy; Pure Al was heated to its melting temperature of 750°C, then pure Cu and Al-10Mn were added. The mixture was kept at this temperature for 30 minutes to allow all the raw materials to melt completely. The surface slag was removed and the mixture was stirred thoroughly. The melt was then poured into a steel mold and cast to obtain a cast Al-Mn-Cu alloy.

[0036] (2) The as-cast Al-Mn-Cu alloy was cold-rolled and deformed by 90%, and then aged to obtain a high thermal stability Al-Mn-Cu alloy.

[0037] The aging treatment temperature was 400℃, and the treatment time was 100 h.

[0038] Example 6 Compared with Example 5, the aging treatment temperature was 400°C, and the treatment times were 0 h, 5 h, 15 h, 35 h, 55 h, 75 h and 100 h.

[0039] Example 7 High thermal stability Al-0.8Mn-2.0Cu alloy: The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 2.0 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

[0040] (1) Weigh out pure Al, pure Cu and Al-10Mn according to the mass percentage of the Al-0.8Mn-2.0Cu composition of the target alloy; Pure Al was heated to its melting temperature of 750°C, then pure Cu and Al-10Mn were added. The mixture was kept at this temperature for 30 minutes to allow all the raw materials to melt completely. The surface slag was removed and the mixture was stirred thoroughly. The melt was then poured into a steel mold and cast to obtain a cast Al-Mn-Cu alloy.

[0041] (2) The as-cast Al-Mn-Cu alloy was cold-rolled and deformed by 90%, and then aged to obtain a high thermal stability Al-Mn-Cu alloy.

[0042] The aging treatment temperature was 400℃, and the treatment time was 100 h.

[0043] Example 8 Compared with Example 7, the aging treatment temperature was 400°C, and the treatment times were 0 h, 5 h, 15 h, 35 h, 55 h, 75 h and 100 h.

[0044] Experimental Example 1 Figure 1 and Figure 2 The conductivity and microhardness of different Al-Mn-Cu alloys in Examples 1 to 8, and the same Al-Mn-Cu alloy under different aging treatment times, are respectively obtained from... Figure 1 and Figure 2 As can be seen, for the same Al-Mn-Cu alloy, the electrical conductivity of the alloy continuously increases with the increase of the holding time at 400℃, reaching a peak after 100 h; the microhardness of the alloy gradually decreases with the extension of aging, and the change in hardness tends to level off after 15 h. Meanwhile, in different Al-Mn-Cu alloys, different Cu addition amounts lead to different electrical conductivity and microhardness at the same treatment time. The results confirm that the Cu addition amount can effectively control the T-phase precipitation behavior and reduce the size of the precipitated phase, such as... Figure 5 , 6 As shown.

[0045] The samples prepared in Examples 1, 3, 5, and 7 were subjected to high-temperature heat resistance tests: The samples were placed in a heat treatment furnace and held at 450℃, 475℃, 500℃, 550℃, 575℃, and 600℃ for 1 hour sequentially. After each temperature holding period, the samples were removed, and their electrical conductivity and microhardness were tested. The criterion for judging heat resistance stability was that the microhardness of the sample maintained 90% of its original hardness. Test Results Figure 3 and Figure 4 As shown in the figure. The test results show that after the four alloys were held at 575℃ for 1 h, the hardness and strength retention rates were both higher than 90%, proving that this series of alloys has both excellent high-temperature heat resistance and electrical conductivity.

[0046] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a high thermally stable Al-Mn-Cu alloy, characterized in that, The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.3 wt%~1.2 wt%, Cu 0.2 wt%~3 wt%, w(Cu) / w(Mn)≥0.77, Fe ≤0.2 wt%, Si ≤0.2 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al. The preparation method includes the following steps: Pure Al, pure Cu, and Al-10Mn were weighed according to their mass percentages, and alloyed to obtain a melt. The melt was then cast to obtain an as-cast Al-Mn-Cu alloy. The as-cast Al-Mn-Cu alloy was cold-rolled to deform it by 85-90%, and then aged to obtain a high thermal stability Al-Mn-Cu alloy.

2. The preparation method according to claim 1, characterized in that, The temperature during alloy smelting is 720~760℃.

3. The preparation method according to claim 2, characterized in that, Alloy smelting methods include: Heat pure Al to 720~760℃, then add pure Cu and Al-10Mn, let stand and keep warm for 20~40 minutes to completely melt all the raw materials, stir evenly, and it is ready.

4. The preparation method according to claim 1, characterized in that, During cold rolling deformation, a two-roll cold rolling mill is used for cold rolling, and the deformation amount per pass is 2% to 4%.

5. The preparation method according to claim 1, characterized in that, The aging treatment temperature is 300~450℃, and the aging treatment time is 75~100 h.

6. The preparation method according to claim 1, characterized in that, The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 0.7 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al. Alternatively, the high thermal stability Al-Mn-Cu alloy may have the following composition by mass percentage: Mn 0.8 wt%, Cu 1.2 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

7. The preparation method according to claim 1, characterized in that, The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 1.6 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

8. The preparation method according to claim 1, characterized in that, The high thermal stability Al-Mn-Cu alloy has the following composition by mass percentage: Mn 0.8 wt%, Cu 2.0 wt%, Fe ≤0.05 wt%, Si ≤0.05 wt%, Ti ≤0.01 wt%, Cr ≤0.01 wt%, V ≤0.01 wt%, Zr ≤0.05 wt%, with the balance being Al.

9. A high thermal stability Al-Mn-Cu alloy, characterized in that, It is prepared by the preparation method described in any one of claims 1 to 8.

10. The application of the high thermal stability Al-Mn-Cu alloy of claim 9 as an aluminum alloy conductor.